Beyond materials: The construction process in space, time and culture in the informal settlement of Mathare, Nairobi. (2021) - Celentano, Giulia; Habert, Guillaume
Abstract: The informal settlements in the Global South, mostly comprising of inadequate building solutions, are growing rapidly, therefore calling for more sustainable construction interventions and upgrading strategies. Within this context, this study considers that appropriate construction strategies are capable of engaging with the local economy, affected by endemic poverty, therefore contributing to the improvement of the settlement's socio-economic and physical conditions at once. A deeper understanding of the settlements construction process, actors, and key factors influencing material use, acceptance, and distribution, is therefore needed, and is here presented for the case of Mathare, in Nairobi. The study is based on field-based qualitative and quantitative data collection through semi-structured interviews and mapping, and through the adoption of methods as stakeholders analysis and supply chain mapping. The following insights have emerged from the study: 1) different client groups have access to different building materials; 2) the distribution of materials inside the settlement is strictly related to stores and building sites accessibility; 3) the local adoption of materials is highly impacted by the availability of space both at the supplier store and on the building site; 4) contextual cultural factors can have a major role in the construction organization. as for the case of ethnicity influencing roles distributions in the construction sector. The study insights are of relevance for the practice, specifically to inform project managers and policymakers involved in construction projects in the informal settlements about local material supply and demand constraints. Specifically, the study highlights the need to consider the availability of stocking space alongside the supply as well as on-site. Finally, it shows the validity of adopting a mixed-methods approach, looking at the settlements through a socio-technical approach. Highlights: The socio-economic, technical and cultural dimensions of the construction practice in the informal settlement of Mathare (Nairobi) are assessed. Different end-users in Mathare have access to different building materials, as the local supply is diversified. Materials diffusion is related to store accessibility, and impacted by space availability by the retailers and on-site. Construction projects accounting for local drivers and bottlenecks can mobilize the local economy. Ethnicity influences roles distribution in the construction sector. Construction projects need to consider the identified socio-technical constraints in order to be inclusive and sustainable.